Working life expectancy of physicians: the case of primary care physicians in Czechia - Tereza Havelková; Luděk Šídlo (Human Resources for Health)
Abstract Background The decrease in the number of healthcare workers and the resulting deterioration in healthcare quality and availability have been subjected to intensive discussion in Czechia in recent years. Estimating future healthcare worker capacities requires a detailed analysis of their “movement” within the healthcare system. This study focuses on exits of the primary care physicians from the healthcare system in Czechia. Methods Using anonymised data obtained from the largest Czech health insurance company (2012–2022), we constructed working life tables and calculated working life expectancy, which indicates the expected average number of remaining years of work at the exact age of the physician. The study focuses on primary care physicians, who are crucial for the effective functioning of the healthcare system. Results At age 50, working life expectancy was 20 years for female physicians and approximately 21 years for male physicians. Over the monitored period, working life expectancy decreased by 1 year for both genders. Gynaecologists had the longest working life expectancy, while dentists had the shortest. Conclusions The decrease in the working life expectancy and the length of tenure indicates the need to create favourable conditions for the extension of the working lives of physicians to avoid early exits from the system.